2004
DOI: 10.1590/s0103-50532004000500007
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of (5R)-4,8-dimethylbicyclo[3.3.0]oct-1(8),3-dien-2-one from (-)-limonene oxide: a novel intermediate to the synthesis of 4-5-5 fused tricarbocyclic core present in terpenic natural products

Abstract: Este trabalho refere-se à síntese enantiosseletiva da dienona (5R) -4,8-dimethylbicyclo[3.3.0]oct-1(8),3-dien-2-one. Este intermediário, pode ser reconhecido como um bloco de construção versátil para a síntese de uma grande variedade de compostos com esqueleto biciclo[3.3.0]octano. A estratégia sintética empregada aqui faz uso da reatividade invertida de um precursor cianoidrina TMS-éter, como equivalente de ânion acila, para promover uma reação de alquilação intramolecular.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Pisoni et al developed an efficient stereoselective route toward dienone 1064 , a versatile building block for the synthesis of natural and nonnatural chiral terpenoids bearing a bicyclooctane framework, starting from ( − )-limonene oxide (Scheme ). Subsequent reaction with hypochloric acid, acid-catalyzed hydrolysis of epoxide function of 1058 , and oxidative cleavage of diol 1059 with sodium metaperiodate afforded the enantiomerically pure keto aldehyde ( − )- 1060 , which was subjected to aldol condensation with piperidine–acetic acid to form the unstable conjugated cyclopentane carbaldehyde 1061 . The latter was cleanly converted into the cyanohydrin TMS ether 1062 by addition of trimethylsilyl cyanide in the presence of KCN/18-crown-6 complex, which was subjected to intramolecular alkylation with lithium hexamethyldisilazide followed by treatment of 1063 with tetra- n -butylammonium fluoride, to form ( − )-( R )- 1064 with the endocyclic C3–C4 double bond as a single isomer in good overall yield.…”
Section: Functionalization Of Chiral Building Blocksmentioning
confidence: 99%
“…Pisoni et al developed an efficient stereoselective route toward dienone 1064 , a versatile building block for the synthesis of natural and nonnatural chiral terpenoids bearing a bicyclooctane framework, starting from ( − )-limonene oxide (Scheme ). Subsequent reaction with hypochloric acid, acid-catalyzed hydrolysis of epoxide function of 1058 , and oxidative cleavage of diol 1059 with sodium metaperiodate afforded the enantiomerically pure keto aldehyde ( − )- 1060 , which was subjected to aldol condensation with piperidine–acetic acid to form the unstable conjugated cyclopentane carbaldehyde 1061 . The latter was cleanly converted into the cyanohydrin TMS ether 1062 by addition of trimethylsilyl cyanide in the presence of KCN/18-crown-6 complex, which was subjected to intramolecular alkylation with lithium hexamethyldisilazide followed by treatment of 1063 with tetra- n -butylammonium fluoride, to form ( − )-( R )- 1064 with the endocyclic C3–C4 double bond as a single isomer in good overall yield.…”
Section: Functionalization Of Chiral Building Blocksmentioning
confidence: 99%
“…[5][6][7] Chlorination represents a valuable pathway to produce versatile starting materials that are widely used in synthetic organic chemistry. [8][9][10][11] Chloride compounds can be prepared directly by bubbling molecular chlorine, but the difficulty of handling chlorine gas limits this procedure. 12 Other authors have shown a convenient method for this transformation using solid CO 2 and calcium hypochlorite 13,14 or a combination of Vilsmeier reagent and H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Since Brazil is the world top producer of orange and its juice (having the peel as a side product), 2 it is economically interesting to give (R)-limonene nobler applications compared to solvent for paint, additive to food, hygiene products or cosmetics and other classical uses of this terpene. 3 (R)-Limonene has two chemically distinct double bonds that make possible a large number of chemical modifications in order to synthesize more complex molecules [4][5][6] with applications spread over medicinal chemistry, [7][8][9][10][11][12][13] total synthesis of natural products, [14][15][16][17][18] and others, including applications in catalysis. The first use of limonenederived chiral ligands in catalytic systems was published by Lahuerta et al 19 in 2000, where the researchers used LiPPh 3 to perform previously reported selective epoxide opening in limonene oxides, 20 generating phosphinealcohols that induced low selectivity in Rh-catalyzed C-H insertion and cyclopropanation reactions.…”
Section: Introductionmentioning
confidence: 99%